Tell Tchaikovsky the News : Rock 'n' Roll, the Labor Question, and the Musicians' Union, 1942-1968 - Roberts, Michael James, 1967- (Book collections on Project MUSE., 2014)
For two decades after rock music emerged in the 1940s, the American Federation of Musicians (AFM), the oldest and largest labor union representing professional musicians in the United States and Canada, refused to recognize rock 'n' roll as legitimate music or its performers as skilled musicians. The AFM never actively organized rock 'n' roll musicians, although recruiting them would have been in the union's economic interest.